IMPLEMENTASI DAN KENDALA SISTEM AKUNTANSI PEMERINTAH DAERAH BERBASIS AKRUAL - ., Risnaningsih (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2016)
abstractHidayatullah (2010) said that the adoption of the accrual system not only aims to standards and formats mere presentation of financial statements, but also have an impact on changing the system of budgeting. In addition, the adoption of accrual accounting system will inevitably affect the performance measurement system and government. In other words, akrualisasi government accounting system in addition to changing the format of financial accountability, will also have an impact on fiscal policy and the government's performance in the future. Each country is also experiencing different obstacles in the application of the accrual basis. Obstacles faced by local governments in the implementation of Government Accounting System accrual (Aaron, 2009: 131) including: preparation of standards that are not independent, the laws are conflicting, the lack of political support government elite, the lack of response from the House of Representatives, the lack of staff quality, constraints accounting reform at the local government level.Keywords: Accounting Systems, Accrual, Government PerformanceÂ abstrakHidayatullah (2010) mengatakan pengadopsian sistem akrual tidak hanya bertujuan standar dan format penyajian laporan keuangan belaka, tetapi juga berdampak pada berubahnya sistem penyusunan anggaran. Di samping itu, pengadopsian sistem akuntansi akrual mau tidak mau akan mempengaruhi sistem dan pengukuran kinerja pemerintah. Dengan kata lain, akrualisasi sistem akuntansi pemerintahan selain merubah format akuntabilitas keuangan, juga akan berdampak pada kebijakan fiskal dan kinerja pemerintah di masa yang akan datang.Setiap negara juga mengalami kendala yang berbeda-beda dalam penerapan basis akrual. Kendala yang dihadapi oleh Pemerintah Daerah dalam penerapan Sistem Akuntansi Pemerintah berbasis akrual (Harun, 2009:131) diantaranya: penyusunan standar yang tidak independen, produk hukum yang saling bertentangan, minimnya dukungan politik elit pemerintah, kurangnya respon dari Dewan Perwakilan Rakyat dan masyarakat, kurangnya staf yang berkualitas, kendala reformasi akuntansi pada tingkat pemerintah daerah.Kata Kunci:Â  Sistem Akuntansi, Akrual, Kinerja PemerintahÂ